Memaknai Teori Belajar: Pemahaman Guru dan Implementasinya pada Pembelajaran Mendalam di Sekolah Dasar - Yessi Fatika Sari; Nava Khoirotun Nisa; Aulya Nanda Prafitasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning theory is the basis for implementing learning forms, but currently its existence is no longer important for teachers to understand because it is not mentioned in learning plans. This study aims to analyze the application of learning theories in elementary schools and understand the extent to which teachers are able to integrate these theories into teaching practices in the era of in deep learning, especially in the Jember City area. This study was conducted in 4 elementary schools in December 2025. The results of observations and interviews showed that the application of learning theories in elementary schools in the Jember City area has taken place in real life through daily learning practices, although 75% of the teachers who responded did not understand or conceptually realize the underlying theoretical foundations. Behaviorist, cognitivism, constructivism, humanism, and nativism theories are applied implicitly and complement each other, so that the ongoing learning practices have contained elements of in deep learning. However, this in deep learning has not been systematically integrated into learning planning and reflection due to teachers' limited understanding of learning theories. Therefore, strengthening teachers' understanding of the relationship between learning theory and in deep learning is an important need so that learning practices can be developed in a more targeted manner to optimize character formation, the development of critical thinking skills and in-depth conceptual understanding in elementary schools